NEW ANDEAN BEE SPECIES OF CHILICOLA SPINOLA (HYMENOPTERA: COLLETIDAE, XEROMELISSINAE) WITH NOTES ON THEIR BIOLOGY - González Victor H; Giraldo Catalina (Caldasia)
We describe and illustrate three new bee species of the genus Chilicola Spinola that occur at high altitudes in the Eastern Andes of Colombia: C. (Anoediscelis) paramoides Gonzalez sp. nov., C. (Hylaeosoma) bochica Gonzalez sp. nov., and C.(Oroediscelis) deborahae Gonzalez sp. nov. We also provide biological notes and discuss the phylogenetic relationships of C. deborahae; nests of this species were found inside dry fl ower stems of Espeletia argentea Humb. & Bonpl. (Asteraceae) and a palynological analysis showed that 80 % of the pollen grains found in brood cells belonged to Arcytophyllum aff. nitidum and A. muticum (Rubiaceae). The ichneumonid wasp Grotea sp. is also recorded parasitizing brood cells of C. deborahae.